TOWARDS SUSTAINABLE FOOD PACKAGING: A COMPARATIVE CHEMICO-TECHNOLOGICAL REVIEW OF SYNTHETIC BIOPOLYMERS - Annisa Ulhusna (Jurnal Sains dan Teknologi Pangan, 2026)
The global movement toward sustainable food packaging is increasingly driven by environmental concerns related to excessive plastic waste and the reliance on petroleum-based polymers. Synthetic biopolymers such as polylactic acid (PLA), polyhydroxyalkanoates (PHAs), and polybutylene succinate (PBS) have emerged as promising alternatives due to their biodegradability, renewability, and compatibility with conventional processing technologies. This article presents a comparative review of these three biopolymers, focusing on their chemical structures, synthesis pathways, mechanical and barrier properties, biodegradability, and environmental performance. The review also examines their practical applications in food packaging, highlighting the specific strengths of each material. Through a comprehensive evaluation of recent literature, this study aims to inform material scientists, food technologists, and packaging developers about the opportunities and challenges associated with the implementation of synthetic biopolymers in sustainable packaging systems. The findings indicate that, although each polymer offers distinct advantages, strategies such as material blending, structural modification, and effective end-of-life management are essential to optimize performance and reduce environmental impact.This review contributes to the growing body of knowledge supporting the development of next-generation biodegradable packaging solutions.